Conditions for the Formation of Wear-Resistant Structures When Strengthening the Surface Layers of Parts - Cherneta, Oleg; Kubich, Vadim; Voloshchuk, Roman; Sasov, Alexander; Korzhavin, Yuriy; ., . (International Journal of Engineering and Technology, 2018)
In the given article special attention is paid to the transformation of the structure of average carbon steels, depending on technological methods of strengthening, the identification of factors influencing the emergence of high-strength structures.  With the help of microstructural, X - ray phase studies, microhardness measurements of certain layers, the main technological parameters and modes of reinforcing workings have been identified, new and innovative combined technologies have been proposed. Based on the analysis of a number of existing technological methods of strengthening the surface layer of structural materials, the dynamics of transformation of their microstructures was researched.  After laser treatment, due to the ultra-high velocity of cooling of crystallized volumes, due to intensive heat removal through the main volume of samples on the surface, a light zone, which is not digestible, is identified and is identified as "structurally martensitic" - gardenain, which is  a kind of classical martensite. Based on the analysis of a number of existing technological methods of strengthening the surface layer of structural materials, the dynamics of transformation of their microstructures was researched.
Keywords: laser treatment; microhardness; structural materials; technologies; Х-ray reseach.